The Influence of Learning Guidance on Students Achievement of Islamic Religion Education - M. Zaenal Abidin (Didaktika Religia, 2019)
This article aims to confirm the influence of learning guidance on students’ achievement of Islamic education. In an educational institution, providing knowledge and understanding of Islamic education is very important. However, the ability of students to capture and understand the material presented is different. To cope with students who are less able to master and understand Islamic education material, madrasas do learning guidance to overcome this problem. This article was written using a quantitative approach, and the type of research is correlation using descriptive analysis survey methods. The population was taken from students of class VI MI Islamiyah Genukwatu Ngoro Jombang with 55 students, and 48 students were selected as samples based on a significance level of 5% with the Isaac & Michael formula. Data were collected through questionnaires and documentation. The calculation of the average Learning Questionnaire results in 53.25, and the standard deviation value 12.227 are classified into a score of 47-63, so it can be seen that the student’s learning guidance is high. While the calculation of learning achievement results using daily test scores, the average value of 80.75 is classified into a score of 71-85 and categorized well. The results of this study indicate that there is an influence of learning guidance on students’ achievement of Islamic education in MI. Islamiyah Genukwatu Ngoro Jombang. This is evident from the results of the SPSS data showing that the correlation coefficient is 0.861, which means significant, so the coefficient of determination obtained is 0.742.